EFEKTIVITAS PELAKSANAAN PERATURAN PEMERINTAH NO. 86 TAHUN 2019 TENTANG KEAMANAN PANGAN TERHADAP PRODUK OLAHAN PANGAN INDUSTRI RUMAH TANGGA YANG TIDAK MEMILIKI IZIN EDAR SERTIFIKAT PRODUKSI PANGAN INDUSTRI RUMAH TANGGA (SPP-IRT) DI KABUPATEN BANYUWANGI - Dita Miranda, Komang (Fakultas Hukum Universitas 17 Agustus 1945 Banyuwangi, 2023)
THE EFFECTIVENESS OF THE IMPLEMENTATION OF GOVERNMENT REGULATION NO. 86 OF 2019 CONCERNING FOOD SAFETY FOR PRODUCTSPROCESSED FOOD IN THE HOUSEHOLD INDUSTRY THAT DOES NOT HAVE A DISTRIBUTION PERMIT FOR FOOD PRODUCTION CERTIFICATESHOME INDUSTRY (SPP-IRT) IN BANYUWANGI REGENCY. Household Industry (IRT) is a type of economic activity in which most of its business activities are centered in a house that has a separate room from other rooms in the residence. IRT activities that have production results in the form of processed food or called Household Industrial Food (P-IRT). Business actors are required to have a distribution permit in the form of a Household Industrial Food Production Certificate (SPP-IRT). The obligation for household industry food business actors to have an SPP-IRT distribution permit is explained in Government Regulation No. 86 concerning Food Safety which states that certain processed foods produced by the household industry are required to have a household industry Processed Food production permit. So that this research has a formulation of problems, namely (1) How is the effectiveness of the implementation of Government Regulation No. 86 of 2019 concerning Food Safety for processed food products of the household industry that do not have an SPP-IRT distribution permit and (2) How to carry out supervision by the Health Office on processed food in the household industry related to SPP-IRT distribution permits in Banyuwangi. In this study, the author uses an empirical type of legal research with a sociological juridical approach, namely looking at a legal reality by examining social symptoms that exist in society directly in the field, data from this study is obtained from data in the field and literature, to be then analyzed more deeply by the author. The results of the study concluded that PP No. 86 of 2019 concerning Food Safety is deemed ineffective because many IRT business actors still do not know about the PP and the importance of P-IRT permits as a form of business legality. The forms of pre-market and post-market supervision applied by the Health Service to IRT business actors are currently less active after the OSS (Online Single Submission) system was introduced because this system was still newly implemented and the implementation of supervision by the Health Service to business actors in Banyuwangi still lacks.